Positive electrode material, preparation method thereof and battery
By covering the co-clad layer of manganese dioxide and aluminum fluoride on the surface of the lithium-rich manganese-based positive electrode material, the problems of its structural instability and high charge transfer resistance are solved, and the rate performance and cycle of lithium-ion batteries are significantly improved. Stability, optimized electrochemical properties.
Patent Information
- Application Number
- CN202411345852.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
During the charging and discharging process, lithium-rich manganese-based positive electrode materials have problems such as structural instability, high charge transfer resistance and poor circulation performance, which affects the rate performance and cycle stability of lithium-ion batteries.
The surface of the lithium-rich manganese-based positive electrode material is coated with a co-clad layer of manganese dioxide and aluminum fluoride. Through the lithium-ion deintercalation activity and physical barrier mechanism, the charge transfer resistance is reduced, and the lithium-ion transmission efficiency and crystal structure stability are improved.
The cycle stability and rate performance of lithium-rich manganese-based positive electrode materials are significantly improved, the electrochemical performance is optimized, the cycle life of the battery is extended, and the charge transfer resistance is reduced.
Smart Images

Figure BDA0005062594980000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a positive electrode material and a preparation method thereof, and a battery. Background Art
[0002] With the rapid development of consumer electronics, electric vehicles and energy storage, there is an urgent need to improve the energy density of secondary energy storage devices represented by lithium-ion batteries. As we all know, the electrochemical performance of lithium-ion batteries is heavily dependent on positive electrode materials. Among them, lithium-rich manganese-based materials have attracted much attention in the new generation of lithium-ion battery positive electrode materials due to their advantages such as high discharge capacity, high discharge voltage, low cost and long cycle life.
[0003] Lithium-rich manganese-based materials have a unique anion redox mechanism, which not only contributes to high specific capacity, but also causes unstable crystal structure of lithium-rich materials, oxygen loss and transition metal migration, which in turn causes problems such as voltage and capacity attenuation during the cycle, lower first-cycle coulombic efficiency and poor cycle performance.
[0004] In response to the above problems, researchers at home and abroad have proposed different solutions such as surface coating, bulk doping, and material composites. Among them, bulk doping can well dope heterogeneous metals or non-metallic elements, inhibiting the irreversible transformation of the layered structure to the spinel phase during the charge and discharge process. However, it cannot guarantee the stable formation of the solid / electrolyte membrane (SEI membrane) during the charge and discharge process. Although material composites can combine the advantages of the two materials, the structural defects of the two materials will also weaken their electrochemical properties. In contrast, coating the surface of lithium-rich manganese-based positive electrode materials with appropriate materials can not only isolate the direct contact between the positive electrode material and the electrolyte, reduce the corrosion of the material, but also improve the surface conductivity. However, there are many types of coating materials. How to combine the characteristics of lithium-rich manganese-based materials to find a more suitable coating method and coating material is of great significance for further improving the electrochemical performance of lithium-rich manganese-based positive electrode materials. Summary of the invention
[0005] In order to solve the problems and shortcomings existing in the prior art, the present invention provides a positive electrode material and a preparation method thereof, and a battery. The positive electrode material is a modified lithium-rich manganese-based positive electrode material, which has good structural stability and low charge transfer resistance, thereby effectively improving the rate performance and cycle stability of the battery.
[0006] According to a first aspect of the present invention, a positive electrode material is provided, comprising a core and a shell covering the core, wherein the core comprises a lithium-rich manganese-based positive electrode material, and the shell comprises manganese dioxide and aluminum fluoride; the chemical formula of the lithium-rich manganese-based positive electrode material is xLi 2 MnO 3 ·(1-x)LiMO 2, M is a transition metal, the transition metal includes at least one of Ni, Co, and Mn, and 0≤x≤1.
[0007] The present invention can effectively improve the cycle stability and rate performance of the lithium-rich manganese-based positive electrode material by coating manganese dioxide and aluminum fluoride on the surface of the lithium-rich manganese-based positive electrode material, and can also effectively reduce the charge transfer resistance, improve the lithium ion transmission efficiency, and optimize the electrochemical performance of the lithium-rich manganese-based positive electrode material. Specifically, manganese dioxide has lithium ion deintercalation activity, can efficiently store and release lithium ions, and also has the characteristics of high capacity. Therefore, manganese dioxide can reduce the charge transfer resistance, improve the lithium ion transmission efficiency, and optimize the cycle rate performance of the lithium-rich manganese-based material. And the coating layer formed by manganese dioxide and aluminum fluoride can physically block the positive electrode material and the electrolyte, prevent the high-valent metal cations and active oxygen species on the surface of the material from reacting with the electrolyte, and can also inhibit the corrosion of HF in the electrolyte. In addition, the coating layer can also limit the active oxygen species generated by charging to the inside of the material to prevent oxygen from escaping, thereby alleviating the problems of low first-cycle coulomb efficiency, poor rate performance and cycle stability of the lithium-rich manganese-based material. Aluminum fluoride is a metal fluoride, which can not only effectively alleviate the occurrence of interface side reactions between electrode materials and electrolytes, but also - It can also reduce the charge transfer resistance, improve the conductivity and crystal structure stability of the positive electrode material, and thus improve the rate performance and cycle stability of the positive electrode material.
[0008] Moreover, the coating layer formed by manganese dioxide and aluminum fluoride can further produce a certain synergistic effect, which can not only improve the crystal structure stability of lithium-rich manganese-based positive electrode materials and optimize their cycle stability during the charge and discharge cycle, but also further reduce the charge transfer resistance, improve the lithium ion transmission efficiency, and optimize the cycle rate performance of lithium-rich manganese-based materials. Therefore, a layer of manganese dioxide + aluminum fluoride co-coating layer coated on the surface of lithium-rich manganese-based positive electrode materials can effectively improve the electrochemical properties of lithium-rich manganese-based materials in all aspects.
[0009] Here it is explained that the lithium-rich manganese-based positive electrode material xLi 2 MnO 3 ·(1-x)LiMO 2 The chemical composition changes with the change of x value, and lithium-rich manganese-based positive electrode materials with different x values can be prepared according to actual needs.
[0010] Preferably, the D50 of the positive electrode material is 100-200nm, and the thickness of the shell is 10-30nm. Preparing layered lithium-rich manganese-based positive electrode materials into nanomaterials helps shorten the Li+ migration path, improve element distribution and the overall chemical environment. However, nanomaterials have a large specific surface area and are easily corroded by the electrolyte, resulting in phase change of the material and ultimately voltage decay. Therefore, alleviating the corrosion of the electrolyte to the material is the key to giving full play to the advantages of nanomaterials. And because Li + The transmission rate directly determines its rate performance. If the exposed crystal surface of the crystal can be controlled during the synthesis process, its rate performance can be improved to a certain extent.
[0011] The surface of the lithium-rich manganese-based positive electrode material in the present invention is coated with a nano-level co-coating layer of manganese dioxide + aluminum fluoride, which can effectively block the contact between the lithium-rich manganese-based positive electrode material and the electrolyte, greatly reducing the degree of side reactions. Therefore, even the nano-level positive electrode material has good structural stability, and can maintain structural stability for a long time during the charge and discharge cycle, prevent material phase change, and avoid rapid voltage decay. However, if the nano-level positive electrode material is too small, it will affect the dispersibility of the subsequent positive electrode slurry, easily aggregate, and affect the coating process, and then affect the stability of the pole piece and the electrochemical properties such as battery cycle performance and rate performance. At the same time, under the D50 of the above-mentioned positive electrode material within a specific range and the coating layer within a specific range, the positive electrode material can not only have excellent lithium ion transmission and conductivity, but also effectively protect the internal lithium-rich manganese-based positive electrode material, so it can effectively improve the electrochemical properties of various aspects of the lithium-rich manganese-based positive electrode material.
[0012] Preferably, the mass proportion of manganese dioxide in the positive electrode material is 1-3%; the mass proportion of aluminum fluoride in the positive electrode material is 1-2%. First, if there is too much manganese dioxide or aluminum fluoride, the co-coating layer of manganese dioxide + aluminum fluoride is thicker, which will lengthen the lithium ion transmission path, which is not conducive to the rapid deintercalation of lithium ions, and affect the cycle performance and rate performance of the material; if there is too little manganese oxide or aluminum fluoride, the co-coating layer of manganese dioxide + aluminum fluoride is thinner, which cannot fully protect the core of the lithium-rich manganese-based positive electrode material, and the side reactions of the electrolyte and the electrode material increase, which deteriorates the lattice stability of the positive electrode material, and also affects the cycle performance and rate performance of the material. And if the proportion of manganese dioxide and aluminum fluoride is too little or too much respectively, resulting in the mass ratio of manganese dioxide to aluminum fluoride not being within a certain range, the synergistic effect of the co-coating layer formed by the two will be worse, resulting in the deterioration of the electrochemical performance of the positive electrode material, deterioration of its cycle performance and rate performance, etc.
[0013] Preferably, the lithium-rich manganese-based positive electrode material includes 0.3Li 2 MnO 3 0.7LiMn 0.5 Ni 0.5 O2 、0.5Li 2 MnO 3 0.5LiNi 0.5 Co 0.2 Mn 0.3 O 2 , Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 , Li 1.2 Ni 0.2 Mn 0.6 O 2 At least one of .
[0014] Preferably, the lithium-rich manganese-based positive electrode material includes Li 1.2 Ni 0.2 Mn 0.6 O 2 .
[0015] The co-coating layer of manganese dioxide + aluminum fluoride can effectively modify the above-mentioned lithium-rich manganese-based positive electrode materials, and can significantly improve the cycle performance and rate performance of lithium-rich manganese-based positive electrode materials, especially for the chemical formula Li 1.2 Ni 0.2 Mn 0.6 O 2 The lithium-rich manganese-based positive electrode material has a more obvious optimization effect.
[0016] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned positive electrode material, comprising the following steps: S1. mixing a lithium source, a manganese source and a transition metal source to prepare a first powder of nanometer size; S2. calcining the first powder at 700-1000°C for 5-20 hours, and obtaining a second powder after cooling; the second powder is a lithium-rich manganese-based positive electrode material; S3. ultrasonically treating manganese dioxide and aluminum fluoride in an alcohol solvent for 4-10 hours to obtain a suspension, adding the second powder to the suspension, mixing at 70-90°C to completely evaporate the solvent, and drying to obtain a third powder; S4. calcining the third powder at 700-1000°C for 5-20 hours, and obtaining a positive electrode material after cooling.
[0017] In the above-mentioned method for preparing the positive electrode material, in S1, the raw materials for preparing the lithium-rich manganese-based positive electrode material are mixed to prepare a first powder of nanometer size, so that the second powder (lithium-rich manganese-based positive electrode material) obtained by calcination is also a nanometer-level powder. After the manganese dioxide and aluminum fluoride are ultrasonically treated in an alcohol solvent for 4 to 10 hours, the particles can be fully dispersed and the particles of the two materials can have a smaller particle size and a more uniform particle size distribution. Therefore, when the nanometer-level second powder is added to the suspension formed by the two materials, the two materials may be firmly attached to the surface of the second powder particles, forming a layer of manganese dioxide + aluminum fluoride co-coating layer with uniform thickness and good density on the surface. As a result, the positive electrode material obtained after further calcination also has a nanometer size. Because its surface is coated with a uniform and dense manganese dioxide + aluminum fluoride co-coating layer, it shows a higher lattice stability and lithium ion transmission performance during the charge and discharge cycle, which greatly optimizes the material's first coulomb efficiency, rate performance and cycle stability.
[0018] Preferably, the specific operation of S1 is: mixing the lithium source, manganese source and transition metal source evenly in a solvent, then putting the obtained mixed system into a template container with a nanostructure, performing a mixing operation at 75-85°C to completely evaporate the solvent, allowing the solid in the mixed system to completely deposit in the pores or on the surface of the template, removing the template, drying, and obtaining a first powder; the solvent includes water.
[0019] Preferably, in S1, the lithium source includes lithium carbonate, the manganese source includes manganese carbonate, and the transition metal source includes nickel carbonate.
[0020] Preferably, in S1, in the template container having the nanostructure, the template pore diameter is 50-150 nm.
[0021] Preferably, in S1, D50 of the first powder is 60-110 nm.
[0022] Preferably, in S2, D50 of the second powder is 90 to 170 nm.
[0023] Preferably, in S2, when the first powder is calcined, the temperature is increased to 700-1000° C. at a heating rate of 4-6° C. / min in an oxidizing gas; in S3, when the third powder is calcined, the temperature is increased to 700-1000° C. at a heating rate of 4-6° C. / min in an oxidizing gas. Calcining the first powder and the third powder at a certain heating rate is conducive to taking into account the volatilization rate of water and the crystal strength, so that the powder particles will not form too many obvious structural defects during the calcination process, and improve the coating effect of the manganese dioxide + aluminum fluoride co-coating layer and the overall structural strength of the calcined product.
[0024] Preferably, the first oxidizing gas and the second oxidizing gas independently include air.
[0025] Preferably, in S3, the feed mass ratio of manganese dioxide and aluminum fluoride is (0.5-3):1, and the total input mass of manganese dioxide and aluminum fluoride is 2-5% of the mass of the third powder. Controlling the feed mass ratio and total input amount of manganese dioxide and aluminum fluoride can ensure that the surface of the lithium-rich manganese-based positive electrode material can be coated with a manganese dioxide + aluminum fluoride co-coating layer of appropriate thickness, and can ensure that the manganese dioxide and aluminum fluoride are at a certain mass ratio, so that the formed manganese dioxide + aluminum fluoride co-coating layer shows a better modification effect on the lithium-rich manganese-based positive electrode material, and further optimize the electrochemical performance of the lithium-rich manganese-based positive electrode material.
[0026] Preferably, in S3, the frequency of the ultrasonic treatment is 18 to 22 kHz. Controlling the ultrasonic treatment frequency within the above range is conducive to producing smaller and more uniform particles, while also avoiding excessive ultrasonic treatment frequency causing excessive ultrasound, resulting in aggregation and crystallization of particles, thereby damaging the dispersion effect of the particles.
[0027] Preferably, in S3, the second powder is preheated to 70-90°C before being added to the suspension. Preheating to 70-90°C is to ensure that the second powder (lithium-rich manganese-based positive electrode material) does not affect the system energy after being added to the manganese dioxide + aluminum fluoride suspension, maintain the stability of the system, and optimize the coating effect.
[0028] Preferably, in S3, the alcohol solvent includes ethanol.
[0029] According to a third aspect of the present invention, a battery is provided, comprising the above-mentioned positive electrode material. The battery prepared using the above-mentioned positive electrode material can maintain long-term crystal stability during the battery charge and discharge cycle, and phase change occurs less, effectively improving the battery's cycle performance and rate performance, because the positive electrode material has excellent lithium ion transmission performance, low charge transfer resistance, and good structural stability. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0031] Example 1
[0032] 1. Preparation of positive electrode materials
[0033] The positive electrode material of the present invention is prepared according to the following steps:
[0034] S1.Li 2 CO3 、NiCO 3 、MnCO 3 The mixture is mixed evenly in water, and then the obtained mixed system is put into a template container with a nanostructure, and a mixing operation is performed at 75 to 85° C. to completely evaporate the solvent, and after the solid in the mixed system is completely deposited in the pores or on the surface of the template, the template is removed and dried to obtain a first powder; the first powder is a nano powder; wherein the Li is calculated according to the molar ratio of Li:Ni:Mn of 1.24:0.2:0.6 2 CO 3 、NiCO 3 、MnCO 3 The D50 of the first powder obtained in this process is 85nm; in the template container having a nanostructure, the pore size in the template is 100nm;
[0035] S2. The first powder is calcined at 850°C for 12 hours, cooled, and ground to obtain a second powder; the second powder is a lithium-rich manganese-based positive electrode material, and the chemical formula of the lithium-rich manganese-based positive electrode material is Li 1.2 Ni 0.2 Mn 0.6 O 2 ; The D50 of the second powder obtained in this process is 120nm;
[0036] S3. Manganese dioxide and aluminum fluoride are ultrasonically treated in an ethanol solvent for 7 hours to obtain a suspension, a second powder is added to the suspension, a mixing operation is performed at 80° C. to completely evaporate the solvent, and the mixture is dried to obtain a third powder; wherein the mass ratio of manganese dioxide to aluminum fluoride is 2:1, and the total mass of manganese dioxide and aluminum fluoride is 3.5% of the mass of the third powder;
[0037] S4. The third powder is calcined at 850°C for 12 hours and cooled to obtain a positive electrode material. The D50 of the positive electrode material is 140nm. After testing, it is found that the coating thickness of manganese dioxide + aluminum fluoride is 15-20nm, the mass proportion of manganese dioxide in the positive electrode material is 2.33%, and the mass proportion of aluminum fluoride in the positive electrode material is 1.17%.
[0038] In the above S1, theoretically, the chemical formula of the obtained lithium-rich manganese-based positive electrode material should be Li 1.2 Ni 0.2 Mn 0.6 O 2 The molar ratio of Li:Ni:Mn is 1.2:0.2:0.6. 2 CO 3 、NiCO 3 、MnCO 3However, in order to compensate for the volatilization of lithium at high temperature, more Li elements need to be added. Therefore, the final Li:Ni:Mn molar ratio is 1.24:0.2:0.6. 2 CO 3 、NiCO 3 、MnCO 3 The feeding amount.
[0039] 2. Preparation of batteries
[0040] a. Weigh the materials according to the mass ratio of the composite positive electrode material: conductive carbon black (Super P): binder (PVDF) of 93:3:4, use N-methylpyrrolidone (NMP) as solvent, and centrifuge the mixture for 10 minutes to obtain a positive electrode slurry;
[0041] b. The positive electrode slurry was coated on the aluminum foil with a thickness of 160 μm by using a coating machine, dried at 120°C for 3 h, and then rolled once on a double-roll roller with a gap of 0.1 mm. The rolled aluminum foil was then transferred to a vacuum drying oven and dried at 120°C for 12 h to completely remove NMP and residual moisture.
[0042] c. Cut the dried electrode into discs with a diameter of 12 mm as the positive working electrode;
[0043] d. Assemble button cells: lithium sheet as negative electrode, polypropylene diaphragm as diaphragm, and 1M LiPF electrolyte 6 , dimethyl carbonate (DMC) and ethylene carbonate (EC) in a 1:1.1 (mass ratio), and CR2032 button cells were assembled in a glove box filled with dry argon.
[0044] Example 2
[0045] 1. Preparation of positive electrode materials
[0046] In the preparation process of the positive electrode material of this embodiment, the size of the template mesopores in the template container with nanostructure in S1 is adjusted to reduce the D50 of the first powder obtained, the size of the template mesopores in the template container with nanostructure is 80nm, and the D50 of the first powder is 60nm; at the same time, the total input mass of manganese dioxide and aluminum fluoride in S3 is adjusted (if the D50 of the first powder is reduced, the D50 of the corresponding second powder and lithium-rich manganese-based positive electrode material will also be reduced. Under the condition of consistent coating thickness, less total input mass of manganese dioxide and aluminum fluoride is required), the specific feed mass ratio of manganese dioxide and aluminum fluoride is 2:1, and the total input mass of manganese dioxide and aluminum fluoride is 3% of the mass of the third powder; the D50 of the final positive electrode material is 100nm, and the thickness of the manganese dioxide + aluminum fluoride co-coating layer is 15-20nm; and after testing, it is found that the mass proportion of manganese dioxide in the positive electrode material is 1.98%, and the mass proportion of aluminum fluoride in the positive electrode material is 1.01%. The rest of the operations are consistent with Example 1.
[0047] 2. Preparation of batteries
[0048] The preparation of the battery in this example is consistent with that in Example 1.
[0049] Example 3
[0050] 1. Preparation of positive electrode materials
[0051] In the preparation process of the positive electrode material of this embodiment, the size of the template mesopores in the template container with nanostructure in S1 is adjusted to increase the D50 of the first powder obtained, the size of the template mesopores in the template container with nanostructure is 135nm, and the D50 of the first powder is 110nm; at the same time, the total input mass of manganese dioxide and aluminum fluoride in S3 is adjusted (if the D50 of the first powder increases, the D50 of the corresponding second powder and lithium-rich manganese-based positive electrode material will also increase. In the case of consistent coating thickness, more total input mass of manganese dioxide and aluminum fluoride is required), the specific feed mass ratio of manganese dioxide and aluminum fluoride is 2:1, and the total input mass of manganese dioxide and aluminum fluoride is 5% of the mass of the third powder; the D50 of the final positive electrode material is 200nm, and the thickness of the manganese dioxide + aluminum fluoride co-coating layer is 15-20nm; and after testing, it is found that the mass proportion of manganese dioxide in the positive electrode material is 2.96%, and the mass proportion of aluminum fluoride in the positive electrode material is 1.55%. The rest of the operations are consistent with Example 1.
[0052] 2. Preparation of batteries
[0053] The preparation of the battery in this example is consistent with that in Example 1.
[0054] Example 4
[0055] 1. Preparation of positive electrode materials
[0056] In the preparation process of the positive electrode material of this embodiment, the total input mass of manganese dioxide and aluminum fluoride in S3 is adjusted, and the specific input mass ratio of manganese dioxide and aluminum fluoride is 1:1, and the total input mass of manganese dioxide and aluminum fluoride is 2% of the mass of the third powder; the D50 of the final positive electrode material is 127nm, and the thickness of the manganese dioxide + aluminum fluoride co-coating layer is 5-8nm; and after testing, it is found that the mass proportion of manganese dioxide in the positive electrode material is 0.99%, and the mass proportion of aluminum fluoride in the positive electrode material is 1.00%. The rest of the operations are consistent with Example 1.
[0057] 2. Preparation of batteries
[0058] The preparation of the battery in this example is consistent with that in Example 1.
[0059] Example 5
[0060] 1. Preparation of positive electrode materials
[0061] In the preparation process of the positive electrode material of this embodiment, the total input mass of manganese dioxide and aluminum fluoride in S3 is adjusted, and the specific input mass ratio of manganese dioxide and aluminum fluoride is 1:1, and the total input mass of manganese dioxide and aluminum fluoride is 4% of the mass of the third powder; the D50 of the final positive electrode material is 157nm, and the thickness of the manganese dioxide + aluminum fluoride co-coating layer is 35-40nm; and after testing, it is found that the mass proportion of manganese dioxide in the positive electrode material is 2.01%, and the mass proportion of aluminum fluoride in the positive electrode material is 1.99%. The rest of the operations are consistent with Example 1.
[0062] 2. Preparation of batteries
[0063] The preparation of the battery in this example is consistent with that in Example 1.
[0064] Example 6
[0065] 1. Preparation of positive electrode materials
[0066] In the preparation process of the positive electrode material of this embodiment, the size of the pores in the template of the template container with nanostructure in S1 is adjusted to increase the D50 of the first powder obtained, the size of the pores in the template of the template container with nanostructure is 120nm, and the D50 of the first powder is 190nm; at the same time, the total input mass of manganese dioxide and aluminum fluoride in S3 is adjusted, specifically the feeding mass ratio of manganese dioxide and aluminum fluoride is 1:1, and the total input mass of manganese dioxide and aluminum fluoride is 6% of the mass of the third powder; the D50 of the final positive electrode material is 230nm, and the thickness of the manganese dioxide + aluminum fluoride co-coating layer is 35-40nm; and after testing, it is found that the mass proportion of manganese dioxide in the positive electrode material is 3.01%, and the mass proportion of aluminum fluoride in the positive electrode material is 3.01%. The rest of the operations are consistent with Example 1.
[0067] 2. Preparation of batteries
[0068] The preparation of the battery in this example is consistent with that in Example 1.
[0069] Example 7
[0070] 1. Preparation of positive electrode materials
[0071] In the preparation process of the positive electrode material of this embodiment, the total input mass of manganese dioxide and aluminum fluoride in S3 is controlled to remain unchanged, but the feeding mass ratio of manganese dioxide and aluminum fluoride is adjusted, and the specific feeding mass ratio of manganese dioxide and aluminum fluoride is 8:1; the D50 of the final positive electrode material and the thickness of the manganese dioxide + aluminum fluoride co-coating layer are consistent with those in Example 1; and after testing, it is found that the mass proportion of manganese dioxide in the positive electrode material is 3.11%, and the mass proportion of aluminum fluoride in the positive electrode material is 0.39%. The rest of the operations are consistent with Example 1.
[0072] 2. Preparation of batteries
[0073] The preparation of the battery in this example is consistent with that in Example 1.
[0074] Example 8
[0075] 1. Preparation of positive electrode materials
[0076] In the preparation process of the positive electrode material of this embodiment, the total input mass of manganese dioxide and aluminum fluoride in S3 is controlled to remain unchanged, but the feeding mass ratio of manganese dioxide and aluminum fluoride is adjusted, and the specific feeding mass ratio of manganese dioxide and aluminum fluoride is 0.4:1; the D50 of the final positive electrode material and the thickness of the manganese dioxide + aluminum fluoride co-coating layer are consistent with those in Example 1; and after testing, it is found that the mass proportion of manganese dioxide in the positive electrode material is 1%, and the mass proportion of aluminum fluoride in the positive electrode material is 2.5%. The rest of the operations are consistent with Example 1.
[0077] 2. Preparation of batteries
[0078] The preparation of the battery in this example is consistent with that in Example 1.
[0079] Example 9
[0080] 1. Preparation of positive electrode materials
[0081] In the preparation process of the positive electrode material of this embodiment, the Li 2 CO 3 、NiCO 3 、MnCO 3 The ratio of lithium-rich manganese-based cathode materials in S2 is 0.3Li 2 MnO 3 0.7LiMn 0.5 Ni 0.5 O 2 Specifically, the Li is calculated according to the molar ratio of Li:Ni:Mn of 1.01:0.27:0.5. 2 CO 3 、NiCO 3 、MnCO 3 The rest of the operations are the same as those in Example 1.
[0082] 2. Preparation of batteries
[0083] The preparation of the battery in this example is consistent with that in Example 1.
[0084] Example 10
[0085] 1. Preparation of positive electrode materials
[0086] In the preparation process of the positive electrode material of this embodiment, the raw material added to S1 is Li 2 CO 3 、NiCO 3 、MnCO 3 、CoCO 3 , and Li is calculated according to the molar ratio of Li:Ni:Mn:Co of 1.01:0.11:0.45:0.11 2 CO 3 、NiCO 3 、MnCO 3 、CoCO 3 The amount of feed makes the chemical formula of the lithium-rich manganese-based positive electrode material in S2 to be Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 The remaining operations are consistent with those in Example 1.
[0087] 2. Preparation of batteries
[0088] The preparation of the battery in this example is consistent with that in Example 1.
[0089] Comparative Example 1
[0090] 1. Preparation of positive electrode materials
[0091] In the preparation process of the positive electrode material of this comparative example, the operations in S3 and S4 are not performed, that is, the second powder (lithium-rich manganese-based positive electrode material) obtained in S2 is directly used as the positive electrode material in this comparative example, that is, the surface of the lithium-rich manganese-based positive electrode material is not coated with a manganese dioxide + aluminum fluoride co-coating layer. The remaining operations are consistent with Example 1.
[0092] 2. Preparation of batteries
[0093] The preparation of the battery in this comparative example is consistent with that in Example 1.
[0094] Comparative Example 2
[0095] 1. Preparation of positive electrode materials
[0096] In the preparation process of the positive electrode material of this comparative example, in S3, only manganese dioxide is used to prepare the suspension, and the input amount of manganese dioxide is consistent with the total input amount of manganese dioxide and aluminum fluoride in Example 1. The remaining operations are consistent with Example 1.
[0097] 2. Preparation of batteries
[0098] The preparation of the battery in this comparative example is consistent with that in Example 1.
[0099] Comparative Example 3
[0100] 1. Preparation of positive electrode materials
[0101] In the preparation process of the positive electrode material of this comparative example, in S3, only aluminum fluoride is used to prepare the suspension, and the input amount of aluminum fluoride is consistent with the total input amount of manganese dioxide and aluminum fluoride in Example 1. The rest of the operations are consistent with Example 1.
[0102] 2. Preparation of batteries
[0103] The preparation of the battery in this comparative example is consistent with that in Example 1.
[0104] Test Case
[0105] 1. Experimental Construction Method
[0106] The batteries prepared in the above examples and comparative examples were tested for first cycle coulombic efficiency, cycle capacity retention, rate performance and transition metal dissolution. The specific testing methods are as follows:
[0107] (1) First cycle coulombic efficiency: After the prepared battery was left to stand for 3 hours, the charge / discharge test was performed on the LAND battery test system with a voltage range of 2.0 to 4.8 V. The charge and discharge specific capacities of the battery at a current of 0.1C were recorded respectively, and the first cycle coulombic efficiency of the battery at a current of 0.1C was calculated. The first cycle coulombic efficiency was calculated as: first cycle discharge specific capacity / first cycle charge specific capacity.
[0108] (2) Cycle capacity retention rate and rate performance (discharge capacity at different rates)
[0109] After the prepared battery was left to stand for 3 hours, the charge / discharge test was performed on the LAND battery test system with a voltage range of 2.0 to 4.8 V. The discharge specific capacity of the battery at currents of 0.1C, 1C, and 5C was recorded respectively, and the capacity retention rate of the battery after 100 cycles at a current of 1C was calculated and recorded. The capacity retention rate was calculated as: 100th cycle discharge capacity / first cycle discharge capacity.
[0110] 2. Experimental results
[0111] The test results of the first cycle coulombic efficiency, cycle capacity retention rate and rate performance of the batteries prepared in the above embodiments and comparative examples are shown in Table 1.
[0112] Table 1 Test results of first cycle coulombic efficiency, cycle capacity retention rate and rate performance of the batteries in the embodiments and comparative examples
[0113]
[0114] As shown in Table 1, the battery prepared by using the positive electrode material prepared by the present invention has good first-cycle coulomb efficiency, rate performance and cycle stability. This is because in the positive electrode material provided by the present invention, a layer of manganese dioxide + aluminum fluoride co-coating layer is coated on the surface of the lithium-rich manganese-based positive electrode material, which can not only physically block the positive electrode material and the electrolyte, reduce side reactions, improve the crystal structure stability of the lithium-rich manganese-based positive electrode material, and optimize its cycle stability during the charge and discharge cycle, but also can further reduce the charge transfer resistance, improve the lithium ion transmission efficiency, and optimize the cycle rate performance of the lithium-rich manganese-based material. Therefore, the battery prepared by it has excellent electrochemical performance, specifically refer to Examples 1 to 10.
[0115] In Comparative Example 1, the surface of the lithium-rich manganese-based positive electrode material is not coated with the manganese dioxide + aluminum fluoride co-coating layer, so it cannot effectively block the contact between the lithium-rich manganese-based positive electrode material and the electrolyte, the degree of side reactions increases, and the stability of the lithium-rich manganese-based positive electrode material decreases during the charge and discharge cycle, deteriorating the first-cycle coulomb efficiency, rate performance and cycle performance of the battery.
[0116] In Comparative Example 2, the outer shell (coating) of the positive electrode material contains only manganese dioxide, and in Comparative Example 3, the outer shell (coating) of the positive electrode material contains only aluminum fluoride, which causes the performance of the batteries in Comparative Examples 2 and 3 to decline. This is because manganese dioxide and aluminum fluoride have a certain interaction, and the lack of one of them will cause the performance of the coating to decline, thereby affecting the electrochemical performance of the positive electrode material and the battery.
[0117] Further comparing Examples 1 to 6, the thickness of the co-coating layer of manganese dioxide + aluminum fluoride in the positive electrode materials in Examples 4 to 5 is too small and too large, respectively, resulting in the battery performance being worse than that in Examples 1 to 3. This is because if the coating thickness is too small, the core of the lithium-rich manganese-based positive electrode material cannot be fully protected, the side reactions of the electrolyte and the electrode material increase, the lattice stability of the positive electrode material is degraded, and the cycle performance and rate performance of the material are also affected; and if the coating thickness is too large, the lithium ion transmission path will be lengthened, which is not conducive to the rapid deintercalation of lithium ions, and the cycle performance and rate performance of the material will be affected. In Example 6, the D50 of the positive electrode material is too large, and the thickness of the co-coating layer of manganese dioxide + aluminum fluoride is too large, which makes the battery performance worse than that of Examples 1 to 5. This shows that D50 and the coating thickness have a certain influence on the various performances of the positive electrode material. Controlling D50 and the coating thickness within a certain range is more conducive to optimizing the electrochemical performance of the positive electrode material and the battery. Further comparing Examples 1 to 3, the battery in Example 1 has better performance in all aspects, that is, at the positive electrode material D50 and the thickness of the manganese dioxide + aluminum fluoride co-coating layer of Example 1, the positive electrode material has better electrochemical properties, which is more conducive to the performance of the battery.
[0118] Comparing Example 1 with Examples 7-8, in the manganese dioxide + aluminum fluoride co-coating layer of Example 7, the mass proportion of manganese dioxide is too large, while in the manganese dioxide + aluminum fluoride co-coating layer of Example 8, the mass proportion of aluminum fluoride is too large, which also causes the battery performance in Examples 7 and 8 to be lower than that in Example 1. This shows that in the co-coating layer formed by manganese dioxide and aluminum fluoride, when the mass ratio of the two is within a specific range, it is more conducive to the two materials to exert a better synergistic effect, thereby further optimizing the positive electrode material and the electrochemical performance of the battery.
[0119] By observing Example 1 and Examples 9 to 10, it can be seen that when other types of lithium-rich manganese-based positive electrode materials are used as the core, the manganese dioxide + aluminum fluoride co-coating layer can also effectively modify them, thereby improving the various electrochemical properties of the lithium-rich manganese-based positive electrode materials.
[0120] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: It comprises a core and a shell covering the core, wherein the core comprises a lithium-rich manganese-based positive electrode material, and the shell comprises manganese dioxide and aluminum fluoride; The chemical formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)LiMO2, where M is a transition metal, and the transition metal includes at least one of Ni, Co, and Mn, and 0≤x≤1.
2. The positive electrode material according to claim 1, characterized in that: The D50 of the positive electrode material is 100-200 nm, and the thickness of the shell is 10-30 nm.
3. The positive electrode material according to claim 1, characterized in that: The mass percentage of the manganese dioxide in the positive electrode material is 1 to 3%; The aluminum fluoride accounts for 1-2% by mass in the positive electrode material.
4. The positive electrode material according to claim 1, characterized in that: The lithium-rich manganese-based positive electrode material includes 0.3Li2MnO3·0.7LiMn 0.5 Ni 0.5 O2、0.5Li2MnO3·0.5LiNi 0.5 Co 0.2 Mn 0.3 O2、Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2、Li 1.2 Ni 0.2 Mn 0.6 At least one of O2.
5. The method for preparing the positive electrode material according to any one of claims 1 to 4, characterized in that: The steps include: S1. Mixing a lithium source, a manganese source, and a transition metal source to prepare a first powder of nanometer size; S2. Calcining the first powder at 700-1000° C. for 5-20 hours, and cooling to obtain a second powder; the second powder is the lithium-rich manganese-based positive electrode material; S3. The manganese dioxide and the aluminum fluoride are ultrasonically treated in an alcohol solvent for 4 to 10 hours to obtain a suspension, the second powder is added to the suspension, and the mixture is mixed at 70 to 90 ° C to completely evaporate the solvent, and dried to obtain a third powder; S4. calcining the third powder at 700-1000° C. for 5-20 hours and cooling to obtain the positive electrode material.
6. The method for preparing the positive electrode material according to claim 5, characterized in that: The specific operation of S1 is: mixing the lithium source, the manganese source, and the transition metal source evenly in a solvent, then putting the obtained mixed system into a template container with a nanostructure, performing a mixing operation at 75-85°C to completely evaporate the solvent, allowing the solid in the mixed system to completely deposit in the pores or on the surface of the template, removing the template, drying, and obtaining the first powder; the solvent includes water.
7. The method for preparing the positive electrode material according to claim 5, characterized in that: In S2, when the first powder is calcined, the temperature is increased to 700-1000°C in a first oxidizing gas at a heating rate of 4-6°C / min; in S3, when the third powder is calcined, the temperature is increased to 700-1000°C in a second oxidizing gas at a heating rate of 4-6°C / min.
8. The method for preparing the positive electrode material according to claim 5, characterized in that: In S3, the feed mass ratio of the manganese dioxide and the aluminum fluoride is (0.5-3):1, and the total input mass of the manganese dioxide and the aluminum fluoride is 2-5% of the mass of the third powder.
9. The method for preparing the positive electrode material according to claim 5, characterized in that: In the step S3, the frequency of the ultrasonic treatment is 18 to 22 kHz.
10. A battery, characterized in that: The positive electrode material comprises the positive electrode material as claimed in any one of claims 1 to 4.
Citation Information
Cited By
LMNO lithium-rich manganese-based all-solid-state lithium battery positive electrode active material and preparation method thereof
CN120072926A